Permeability Behavior of Sand-Kaolin Mixtures through Laboratory Tests (International Journal of Innovative Research in Computer Science & Technology, 2022)
Permeability or Hydraulic conductivity of  soil is basic property of soil that needs to be taken into  consideration when planning a Civil engineering project.  In most of the Civil engineering projects a low permeable  soil is desired over high permeable soils. In areas like  deserts, the construction industry is facing a number of  challenges due to non availability of permeable soils.  Kaolin is a naturally occurring fine grained clayey soil that  can be obtained in abundance at very low costs. In this  study samples with different proportions (0%, 5%, 10%,  15%, and 20%) of sand-Kaolin were tested for the  variations in permeability (vertical permeability) of sand.  The tests were performed through constant head  permeability methods and variable head permeability  methods. The main aim of our study was to test the  capability of Kaolin to decrease the permeability of sand.  The results indicated a steep decrease in permeability of  sand till 10% Kaolin clay content, afterwards a gradual  decrease was observed. The coefficient of permeability of  sand was decreased by 99.3% by increasing Kaolin content  to 10% from 0%. This low permeable sand thus obtained  could be potentially used as a filler material, vertical  backfills to cut off the seepage through sandy soils, low  permeable embankments, etc.
Keywords: Permeability; Seepage; Sand- Kaolin mixture; coefficient of permeability; Particle size distribution